Role of Emotional Intelligence in Conflict Management Strategies of Nurses - Ceyda Başoğul, MD, RN; Gönül Özgür, PhD, RN (Elsevier, 2016)
Purpose: This study analyzes the emotional intelligence levels and conflict management strategies of nurses and the association between them. Methods: This cross-sectional, descriptive study was conducted with 277 nurses in a stratified random sample from a university hospital in Turkey. The data were collected from nurses who gave their informed consent to participate using a personal information form, the Rahim Organizational Conflict Inventory-II and Bar-On's Emotional Quotient Inventory (EQ-I). Data were assessed by descriptive statistics, t tests, and Pearson correlation analyses, using SPSS software. Results: The levels of the nurses' strategies were as follows: avoiding (M = 2.98), dominating (M = 2.76), and obliging (M = 2.71) were medium; compromising (M = 1.99) and integration (M = 1.96) were low. The levels of the emotional intelligence of nurses (mean = 2.75) were medium on a 5-point scale. Integration (r = .168), obliging (r = .25), dominating (r = .18), and compromising (r = .33), which are conflict management strategies, were positively correlated with scores of emotional intelligence, and avoiding (r = −.25) was negatively correlated with scores of emotional intelligence (p < .05). Conclusions: The study determined that nurses' emotional intelligence affects conflict management strategies. To use effective strategies in conflict management, nurses must develop emotional intelligence. Training programs on conflict management and emotional intelligence are needed to improve effective conflict management in healthcare facilities.